Aftershocks of shallow earthquakes near Kamchatka Peninsula - Zobin, Vyacheslav M.; Ivanova, Elena I. (Geophysical Journal International, 1992)
We considered aftershock sequences of earthquakes with magnitude M = 4.0–7.8 recorded near the Kamchatka Peninsula coast at depths of 0–59 km in 1962–1987. The events of magnitude M > 1.0 that occurred in the 3 days following the main shock and located not further than 50 km from the main shock epicentre were recognized as aftershocks. Two types of aftershock sequences were distinguished: quakes with one to four aftershocks and quakes having more numerous aftershocks. Aftershock sequences of the first type comprise the majority of the considered events (more than 80 per cent). They are distributed within the overall seismic zone. Aftershock sequences of the second type tend to cluster in space. This type of aftershock sequence zoning can be a useful supplement to standard seismic zoning. The space distribution of the second type of aftershock was used to estimate the dimensions of the source of the main shock. A correlational dependence of source length and area upon energy, magnitude and seismic moment was obtained. Comparison of these estimates of source dimensions with those obtained from P -wave spectra corner frequencies shows good agreement. It has been shown that there exists a linear dependence between energy of the main shock and energetic difference between the main shock and the largest aftershock.